2014
DOI: 10.1007/s12033-014-9742-4
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR Quantification of the Plant Growth Promoting Bacteria Herbaspirillum seropedicae Strain SmR1 in Maize Roots

Abstract: The plant growth promoting bacteria Herbaspirillum seropedicae SmR1 is an endophytic diazotroph found in several economically important crops. Considering that methods to monitor the plant-bacteria interaction are required, our objective was to develop a real-time PCR method for quantification of PGPB H. seropedicae in the rhizosphere of maize seedlings. Primer pairs were designed, and their specificity was verified using DNA from 12 different bacterial species. Ten standard curves of qPCR assay using HERBAS1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 45 publications
4
32
0
1
Order By: Relevance
“…However they were only able to detect H . seropedicae SmR1 in maize roots in non-sterile soil and did not perform any quantification of bacteria [ 38 ]. Von Felten et al described a qPCR protocol to detect 3 Pseudomonas fluorescens strains in maize rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…However they were only able to detect H . seropedicae SmR1 in maize roots in non-sterile soil and did not perform any quantification of bacteria [ 38 ]. Von Felten et al described a qPCR protocol to detect 3 Pseudomonas fluorescens strains in maize rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of replicates in our study was small (6) our results corroborate those of Chiarini et al (1998) , who found that isolates belonging to the genera Burkholderia and Enterobacter co-inoculated in the sorghum rhizosphere promoted a significant increase in root growth compared to non-inoculated plants. Furthermore, species belonging to the genera Burkholderia and Herbaspirillum promote the growth of sugarcane and maize ( Pereira et al, 2014 ; Da Silva et al, 2016 ), which, like sorghum, are C4 grass species. H. frisingense strain IAC/BECa 152 produces siderophores and IAA, whereas Burkholderia tropica strain IAC/BECa 135 does not.…”
Section: Discussionmentioning
confidence: 99%
“…The authors evaluated the survival of these strains through the gastrointestinal tract by qPCR with the strain-specific primers, where they monitored the cell numbers before and after the administration of fermented milk containing this strain. Pereira et al (38) developed a qPCR method for the quantification of the plant growth-promoting bacterium H. seropedicae in the rhizosphere of maize seedlings. Primer pairs were designed from the genome sequence of H. seropedicae SmR1 (39) and tested against 12 different species.…”
Section: Discussionmentioning
confidence: 99%